CO EXISTENCE OF AMPC AND EXTENDED SPECTRUM BETA LACTAMASES RESISTANCE IN METALLO BETA LACTAMASES PRODUCING STRAINS OF PSEUDOMONAS AERUGINOSA - DR. VIKAS MISHRA; DR. PRATIMA GUPTA; DR. BARNALI KAKATI (International Journal of Pharma and Bio Sciences, 2014)
Pseudomonas aeruginosa is one of the commonest multi drug resistant bacteria causing nosocomial infection and Metallo-Beta-Lactamase production is one of the important reasons. The following study was conducted to determine incidence of MBL producing P.aeruginosa. and co existence of AmpC and ESBL production. Screening for MBL was done using imipenem disk and all the isolates found resistant were further subjected to phenotypic confirmation of MBL production using Disc Potentiation test, Modified Hodge test and E- test. Out of 220 isolates screened, 14 were detected to be imipenem resistant; all 14 were positive by Disc Potentiation test and E-test (6,36%) and only 11 isolates were positive by Modified Hodge test. Out of 14 MBL producing isolates, 8 were AmpC producers (57.14%) and all were ESBL producers. Imipenem (carbapenems) use should be restricted and used only in life threatening conditions or in Multi Drug Resistant isolates like P.aeruginosa.